Fungal Melanin: What do We Know About Structure? - Nosanchuk, Joshua D.; Stark, Ruth E.; Casadevall, Arturo (Frontiers in Microbiology, 2015)
The production of melanin significantly enhances the virulence of many important human pathogenic fungi. Despite fungal melanin’s importance in human disease, as well as melanin’s contribution to the ability of fungi to survive in diverse hostile environments, the structure of melanin remains unsolved. Nevertheless, ongoing research efforts have progressively revealed several notable structural characteristics of this enigmatic pigment, which will be the focus of this review. These compositional and organizational insights could further our ability to develop novel therapeutic approaches to combat fungal disease and enhance our understanding of how melanin is inserted into the cell wall.